Monitoring Carbon Dioxide and Methane Levels above Retired Landfill and Forest Control Site with a Tethered Aerostat to Determine Remediation Effectiveness - Banick, Jesse Lee; Zolkowski, Jeshanah Jean; Lenz, Kathryn Elizabeth; Sanders, Jonathan (Proceedings of the Wisconsin Space Conference, 2016)
Â The chemical composition of the ambient air not only affects the health of human beings, but also the health of the planet. This study examined how the decay of waste matter influenced the concentration of carbon dioxide and methane in ambient air. By measuring the level of these two gases above a forest control site and a retired landfill site, the researchers analyzed the effectiveness of the remediation methods utilized on the retired landfill in reducing carbon dioxide and methane emissions. Two carbon dioxide sensors, affixed to a payload, hung beneath a tethered aerostat. The collected data seemed to show that the concentration of carbon dioxide on the retired landfill was equal to the concentration at the control site. However, as the data may have been influenced by sensor limitations, more analysis needs to be done to make conclusions about the remediation effectiveness. Â